2023
DOI: 10.1002/jha2.808
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of UBTF tandem duplications in remission in acute myeloid leukaemia

Sean Harrop,
Phillip C. Nguyen,
David Byrne
et al.

Abstract: UBTF tandem duplications are recurrent in adult and paediatric acute myeloid leukaemia and have been reported to be associated with a poor prognosis. Co‐mutations in WT1 and FLT3 are common while morphological dysplasia is frequent. The role of UBTF‐TDs in leukemogenesis is yet to be elucidated; however they have been proposed as early initiating events, making them attractive for assessment of MRD and a potential therapeutic target. We present two cases where the UBTF‐TD was observed in remission and discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(36 reference statements)
1
1
0
Order By: Relevance
“…These findings are consistent with the recognition of UBTF -TD alterations in nearly a third of pediatric patients with high-grade MDS 24 and recent studies have also identified the persistence of UBTF -TD in remission samples in patients with UBTF -TD myeloid neoplasms. 22 These collective data support the conclusion that UBTF-TD alterations can lead to both MDS and AML, and that UBTF-TD myeloid neoplasms should be recognized as a separate entity.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These findings are consistent with the recognition of UBTF -TD alterations in nearly a third of pediatric patients with high-grade MDS 24 and recent studies have also identified the persistence of UBTF -TD in remission samples in patients with UBTF -TD myeloid neoplasms. 22 These collective data support the conclusion that UBTF-TD alterations can lead to both MDS and AML, and that UBTF-TD myeloid neoplasms should be recognized as a separate entity.…”
Section: Discussionsupporting
confidence: 64%
“…Myelodysplasia-related chromosomal changes or myelodysplasia-related mutations were overall rare, suggesting that UBTF -TD itself contributes to dysplastic features ( Online Supplementary Table S4 ). Considering these overall features and other recent publications, 5 , 8 , 9 , 22 , 23 the majority of UBTF -TD AML (83/89, 93.3%) are best classified as “Acute myeloid leukemia with other defined genetic alterations” in the current WHO classification 20 ( Online Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 69%